The role of estrogens in osteosarcopenia: from biology to potential dual therapeutic effects. (2nd January 2022) - Mandelli, A.; Tacconi, E.; Levinger, I.; Duque, G.; Hayes, A.
Abstract: Osteoporosis and sarcopenia are two conditions associated with aging and characterized by a simultaneous decline in bone and muscle mass, respectively. These conditions share common risk factors (genetic, endocrine, nutritional and lifestyle factors) and biological pathways that often co-exist in a syndrome known as osteosarcopenia. Among the endocrine causes, estrogens play a critical role, especially in women. Estrogens have been demonstrated to exert a positive effect on bone and muscle development and maintenance. For this reason, menopause is characterized by a loss in bone mineral density and skeletal muscle quality and quantity. To date, studies indicate a positive effect of hormonal therapy on the prevention and management of osteoporosis, to the point that estrogen is prescribed as a first-line treatment for osteoporosis by the major international authorities. While results on sarcopenia are still disputable, such that estrogens are not recommended to prevent muscle loss in postmenopausal women, increased response to anabolic stimuli with estrogen therapy suggests similar beneficial effects on muscle as seen with bone, particularly when combined with resistance exercise.